Residual drift mitigation for bridges retrofitted with buckling restrained braces or self centering energy dissipation devices. (15th November 2019) - Upadhyay, A.; Pantelides, C.P.; Ibarra, L.
Highlights: Higher peak and residual drift demands were observed for far-field compared to near-field ground motions. Fragility curves of the as-built and retrofitted bridge bent were developed. BRBs and SCEDs significantly improved the seismic performance of the bridge bent. SCEDs reduced the residual drift ratio and enhanced seismic resiliency. Abstract: A three-column reinforced concrete bridge bent that did not have reinforcement details necessary to provide adequate load capacity and displacement ductility was evaluated under seismic excitations. Two retrofit methods for improving its seismic performance were examined: (i) Buckling Restrained Braces (BRBs), and (ii) Self Centering Energy Dissipation devices (SCEDs). The numerical model of the bridge bent was validated with previous in-situ quasi-static experiments of a full-scale bent. The BRB inelastic behavior was modeled using isotropic and kinematic strain hardening properties. Flag-shaped hysteresis with slip deformation and bearing were used to model the SCED. The numerical models of the BRB and SCED were validated with full-scale experiments of the brace members. Nonlinear time-history analysis was carried out using far-field and pulse-type ground motion sets to evaluate the seismic performance of the as-built and retrofitted bridge bents in the transverse direction. The performance limit states were defined using HAZUS criteria. Incremental dynamic analysis (IDA) was implemented to evaluate the performance of the two retrofit methods up to the collapse limit state. The results show that a retrofit with either BRBs or SCEDs improves the seismic performance of the bridge bent by decreasing drift ratio demands, and reducing the maximum steel and concrete column strains. The BRB and SCED braces reduce damage to the concrete columns by dissipating a significant portion of the input seismic energy. SCED retrofit reduces the bridge bent residual drift ratio under strong earthquakes to acceptable levels; this improves post-earthquake serviceability, increases bridge resilience and keeps repair costs low. Bridge bent peak and residual drift ratio demands were found to be higher under far-field ground motions compared to pulse-type ground motions.